SEJARAH SINGKAT MASUK DAN BERKEMBANGNYA AGAMA BUDHA DI SUMATERA SELATAN - Nur Fitriyana (JIA (Jurnal Ilmu Agama), 2015)
The almost comprehensive note about Buddhism in The Archipelago is written by I’tsing. The note was made in 672 when he had stayed for six month in Sriwijaya to learn Sanskrit before he learned Buddhism in India. From the note, it is known that Srivijaya was the center of Buddhist study in Asia and had close relation to the Buddhist schools in India. There were many pupils from China and Tibet who studied Buddhism in Srivijaya.  Unfortunately, the fame of Buddhism in Srivijaya has disappeared for almost three millennia. In 1954, the commomeration of 2500 years on the development of Buddhism was held in Indonesia. The moment was considered as the Buddhism revivalism in Indonesia dubbed as Buddha Jayanti moment.